Komunikasi Transendental Praktisi Supranatural Dengan Khodam Untuk Penyembuhan Penyakit Non Medis - Genik Puji Yuhanda (Program Studi Hubungan Masyarakat Politeknik LP3I, 2020)
ABSTRACT Transcendental communication is a form of communication that humans make almost every day with God. Apart from God, transcendental communication activities are carried out with angels, jinn or other supernatural beings. If transcendental communication activities are carried out between humans and angels, it can only be done by humans from among the saints of Allah. There are also transcendental communication activities carried out by humans with jinn, which can be carried out by humans who have inherited spiritual abilities because of their ancestral factors who also have the ability to communicate with the supernatural. In addition, transcendental communication with jinn can be done by studying from supernatural experts. In the context of this research, the invisible realm (jinn) is called khodam or